2001
DOI: 10.2466/pms.2001.93.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Repeatability of the Yale Physical Activity Survey in Assessing Physical Activity of Older Adults

Abstract: The purpose of this study was to extend the initial evaluation of the Yale Physical Activity Survey to assess physical activity in older adults. The survey yields three indicators of physical activity reflecting activities performed during a typical week of the previous month (Total Time, Total Energy Expenditure) and the past month (Total Activity Summary Index). Questionnaire validity was studied in 56 men and women, ages 56 to 86 years, by comparing the average of 3- or 7 day 24-hr. physical activity record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
1
13
1
1
Order By: Relevance
“…The test-retest reliability of the YPAS-queried sitting time in the current study is slightly better than has been previously reported 31,39,40 ; likely due to a 10-day measurement period being easier to recall compared to 2-week or longer recall periods. To date, the criterion-related validity of the YPAS to measure time spent in SB in older adults using accelerometer-derived SB time as the criterion has not been investigated.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The test-retest reliability of the YPAS-queried sitting time in the current study is slightly better than has been previously reported 31,39,40 ; likely due to a 10-day measurement period being easier to recall compared to 2-week or longer recall periods. To date, the criterion-related validity of the YPAS to measure time spent in SB in older adults using accelerometer-derived SB time as the criterion has not been investigated.…”
Section: Discussioncontrasting
confidence: 79%
“…However, several studies 31,39–41 have compared this survey’s sitting index to several physical activity-related constructs, including predicted maximal oxygen consumption, anthropometric measures, cardiovascular-related measures, and total accelerometer-derived physical activity counts, to examine its construct validity. Significant correlations were found between the YPAS sitting index and diastolic blood pressure (r = 0.53, P = 0.01) 31 , weight (r = 0.20, P = 0.048) 39 , and skinfold measures (r = 0.02, P = 0.03) 40 . No studies found significant inverse correlations between the YPAS sitting index and estimated oxygen consumption or accelerometer-derived physical activity counts.…”
Section: Discussionmentioning
confidence: 93%
“…This may have increased their awareness about PA probably leading to an underestimation of the reproducibility of the FPACQ (Wendel-Vos, Schuit, Saris, & Kromhout, 2003). In addition, as pointed out by Schuler, Richardson, Ochoa and Wang (2001), it is possible that the first FPACQ administration served as a form of "primer" (i.e., participants may have paid closer attention to their activities after the first administration of the survey). Therefore, the discrepancy between the first and second administration may reflect a more accurate recall on the second administration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, correlations between summary scores from the Community Healthy Activities Model Program for Seniors (CHAMPS) Physical Activity Questionnaire and various measures of physical functioning ranged between 0.10 and 0.54 [16,18-20]. For the CHAMPS Physical Activity Questionnaire and the Yale Physical Activity Survey, test-retest reliability was evaluated over a similar interval to this study (one to two weeks), and ICCs ranged from 0.55 to 0.79 [18,19,21]. …”
Section: Discussionmentioning
confidence: 80%